2017
DOI: 10.1039/c7ay02174g
|View full text |Cite
|
Sign up to set email alerts
|

Different molecular weight chitosan derivatives employed for enantiomeric separation

Abstract: The interaction between two single enantiomers in a racemic mixture impacts the chromatographic retention of the enantiomers to different degrees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…To date, the impact of the molecular weight of cellulose/ amylose on the enantioseparation performance of the corresponding CSPs have been reported in only few studies [37][38][39]. Bai et al have also reported some studies on the relationship between the molecular weight of the chitosan derivatives and their performance, including the chiral recognition ability and mobile phase tolerance of the CSPs [30,32,36,[40][41][42]. Most of these studies indicated that chitosan derivatives with a lower molecular weight showed better enantioseparation performance, but a higher molecular weight was more preferable to tolerate the organic solvents used.…”
Section: Chitosan Derivatives As Chiral Stationary Phases For Hplcmentioning
confidence: 99%
“…To date, the impact of the molecular weight of cellulose/ amylose on the enantioseparation performance of the corresponding CSPs have been reported in only few studies [37][38][39]. Bai et al have also reported some studies on the relationship between the molecular weight of the chitosan derivatives and their performance, including the chiral recognition ability and mobile phase tolerance of the CSPs [30,32,36,[40][41][42]. Most of these studies indicated that chitosan derivatives with a lower molecular weight showed better enantioseparation performance, but a higher molecular weight was more preferable to tolerate the organic solvents used.…”
Section: Chitosan Derivatives As Chiral Stationary Phases For Hplcmentioning
confidence: 99%